(untitled) (TAMADDUN NURI JURNALI, 2024)
The article is dedicated to the study of English place names associated with hydronyms. It analyzes the influence of natural geographic factors and historical processes on the formation of place names. The focus is primarily on formants such as -ford (river crossing point) and -mouth (river mouth). These names reflect various linguistic and ethnic layers: Celts, Anglo-Saxons, Normans, and others. Through place names, it is possible to gain insights into cultural integration and historical geography.